Turkey Reading Culture Map. - Rahmi Akkılık (Türk Kütüphaneciliği)
Derived from the project with the same name, the work was published into a book by the Ministry of Culture and Tourism, Directorate General of Libraries and Publications, the project coordinator. Goal of the project is defined as follows: "specifying the solutions to problems faced directly or indirectly in accessing information, making suggestions to related corporations and persons, determining the perception of libraries in the society, raising the quality of services provided at public libraries and children's libraries affiliated with the Ministry, diversifying these libraries and designating the road map for the future." Carried out with the "method of face-to-face surveys" with 6.212 people in 26 cities, the research revealed the society's habits of reading and library usage.